Examining the Experiences of College Students Simulating the Community Worker Role in the Community Action Poverty Simulation - Jessica M. Limbrick; Portia Johnson; Sheri Worthy; Diann C. Moorman; Leigh Anne Aaron (Journal of Human Sciences and Extension)
Poverty is a pervasive issue impacting many areas of human sciences and Extension. Individuals living in the United States may have varying attitudes toward poverty. Research has shown that poverty simulations are effective in modifying attitudes toward poverty. The Community Action Poverty Simulation (CAPS) program is one such example that exposes its participants to the lived realities of poverty in the United States. While research on CAPS is plentiful, little research has examined the experiences of those who simulated the community worker role. This research explored the experiences of students who simulated community worker roles during a CAPS simulation. This research used the Reflexive Thematic Analysis approach to analyze 50 sampled student reflection papers. The students were enrolled in a large, public land-grant institution in the Southeast. All students completed a family resource management course in either Fall 2015, 2016, 2017, 2018, or 2019. Students shared that they learned about poverty by observing other students. They also expressed their intentions of donating, volunteering, and avoiding judgment of those living in poverty. This research contributes to the literature on CAPS outcomes, specifically for supporting community worker roles.